Women and War in Roman Epic - Pyy, Elina, (The Language of Classical Literature ;, 2021)
In Women and War in Roman Epic , Elina Pyy discusses the narrative and ideological functions of gender in the works of Virgil, Lucan, Statius, Silius Italicus and Valerius Flaccus. By examining the themes of violence, death, guilt, grief, and anger in their epics, she offers an account of the intertextual tradition of the genre and its socio-political background. Through a combination of classical narratology and Julia Kristeva's subjectivity theory, Pyy scrutinises how gendered marginality is constructed in the genre and how it contributes to the fashioning of Roman imperial identity. Focusing on the ambiguous elements of epic, the study looks beyond the binary oppositions between the Self and the Other, male and female, and Roman and barbarian.